Resveratrol loaded in cationic glucosylated liposomes to treat Staphylococcus epidermidis infections. (March 2022) - Pagano, Livia; Gkartziou, Foteini; Aiello, Stefano; Simonis, Beatrice; Ceccacci, Francesca; Sennato, Simona; Ciogli, Alessia; Mourtas, Spyridon; Spiliopoulou, Iris; Antimisiaris, Sophia G.; Bombelli, Cecilia; Mancini, Giovanna
Abstract: Glucosylated liposomes composed of the natural saturated phospholipid 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC), cholesterol (Chol) and a cationic amphiphile featuring a glucosyl moiety (GL4 ), have been developed for delivering the antimicrobial trans -Resveratrol (RSV) to S. epidermidis, characterized by carbohydrate-specific adhesins able to recognize glucose . The cationic derivative of cholesterol, DC-Chol, was also included in liposome formulations, alone or in combination with GL4, in order to explore the role of both cationic charge and sugar moiety in the interaction of liposomes with bacterial cells. RSV was included inside glucosylated cationic liposomes by the thin film method, coupled with either extrusion or sonication; liposome mean diameter, polydispersity index, surface charge, RSV entrapment efficiency and concentration have been measured by DLS, electrophoretic mobility, and HPLC. The antimicrobial activity of RSV-loaded liposomes was evaluated by monitoring the bacterial growth curves of two cell lines of Staphylococcus epidermidis, a slime positive strain (i.e. a strain able to form a biofilm) and a slime negative one. Results point out that, when the glucosylamphiphile GL4 is included in the formulation, only the extrusion protocol allows obtaining monodisperse liposomes with high RSV entrapment efficiency. The mean diameters of empty and resveratrol-loaded liposomes are all around 120–140 nm and size distribution are narrow, except for samples including GL4 at 5 molar percentage. Here the higher polydispersity index may be the indication of the occurrence of a restructuring phenomenon. The microbiological tests put in evidence a different response of the two bacterial cell lines to liposome treatments, in fact, the slime negative bacterial cells, that are not able to produce the extracellular polymeric substances, are more susceptible to the cationic charge of the liposomes and to the detergent effect of GL4 . The most interesting results concern DPPC/Chol/GL4 liposomes on the slime positive strain: this formulation, non-toxic in itself, displays an enhanced antibacterial efficacy with respect to free RSV, killing bacteria even at concentration tenfold under the MIC. Graphical Abstract: ga1 Highlights: Resveratrol glucoliposomes to treat Staphylococcus epidermidis infections. Glucosyl-amphiphile targets Staphylococcus epidermidis . Cationic glucosyl-amphiphile enhances liposomes binding to Staphylococcus epidermidis . Cationic glucosylated liposomes improve resveratrol efficacy against Staphylococcus epidermidis . RSV-loaded in cationic glucosylated liposomes kills Staphylococcus epidermidis at concentration tenfold under the MIC.